Working Conditions in Argentina’s Academia : different career paths and fragmentation of the profession - Marquina, Mónica María; Mendonça, Mariana; Reznik, Nicolás (Hiroshima University, 2024)
Since the mid-twentieth century, higher education systems worldwide have gone through huge transformations as a consequence of massification and the recognition of knowledge as key for economic development. The emergence of new teaching modes, the intensity of research, and performativity and accountability pressures impacted directly on academic work, and as a result, on academic working conditions. In this article, we examine the changes that the Argentine professoriate has experienced in recent decades. We argue that the process of fragmentation of the academic profession presents particularities in regard to global trends. The main goal is to analyze the current state and evolution of the academic workforce in Argentina’s public universities by identifying and characterizing different academic groups. We will focus on different aspects related to the academic profile: gender, training, working conditions, employers, positions, types of contracts, academic practice, perceptions about the career, preferences, and job stress/satisfaction. To achieve this, we have relied on data from the Academic Profession in the Knowledge-Based Society (APIKS) survey.
Keywords: Ciencias Sociales; Ciencias de la Educación